Rezim Kerjasama Sosek Malindo Kaltim-Sabah: Mengukur Derajat Compliance Partisipan Perjanjian - Sonny Sudiar (Universitas Muhammadiyah Yogyakarta, 2014)
Sosek Malindo cooperation is mutual agreement between Indonesia and Malaysia that concentrated in the field of socio-economic development in border areas. The main objective of Sosek Malindo cooperation is to improve the welfare of the people who live in border areas of each country. Sosek Malindo Cooperation produce some agreements, but not all of them can be implemented, because of compliance problems. The failure was caused by several factors, among others: the limited authority of the actor, the factor of interest, in managing the agreement Sosek Malindo regime does not use persuasive methods. Moreover it has serious implications to the implementation of agreement and actor behavior.